CBC broadcasts 1964-1967 : conversations with Glenn Gould, anthology of variation. Duo /. - Bach, Johann Sebastian 1685-1750 (Sony Music Entertainment, 2012)
Emisiones televisivas con presentaciones, comentarios y entrevistas con el pianista Glenn Gould.